Analisis Penggunaan Fitur Chat pada Situs E-Commerce dalam Membangun Reputasi Perusahaan Studi Kasus PT Sanwell Austindo - Riani Karlina Marta; Nani Kurniasari (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2021)
E-Commerce is a development of technology. This study aims to analyze the usage of chat functions on e-commerce used by PT Sanwell Austindo in building the company's reputation so that we can find out the role of chat functions on e-commerce that has an impact on the company's sustainability. This research uses constructivism paradigm, case study method, qualitative approach, type of descriptive research, with data collection techniques obtained from semistructured interviews and documentation. The findings were chosen because the chat functions as a communication channel of PT Sanwell Austindo need a response speed. These characteristic uses are considered effective in communicating messages and can create a sense of trust. Consumer satisfaction takes precedence because it is the basis for the company's reputation. In it’s future business strategy, PT Sanwell Austindo applies consumer trust, innovation, social responsibility, internal company guidance, and completes product descriptions online market to be more informative.